Use of Nasotracheal Intubation during General Anesthesia in Two Ponies with Tracheal Collapse - Ida, Keila K.; Sauvage, Aurélie; Gougnard, Alexandra; Grauwels, Magda; Serteyn, Didier; Sandersen, Charlotte (Frontiers in Veterinary Science, 2018)
Ponies with tracheal collapse may have an increased anaesthetic risk due to airway obstruction during induction and recovery. To our knowledge, there are no anaesthetic descriptions of these patients, despite a reported 5.6% incidence and 77% mortality rate. Two Shetland ponies with tracheal collapse, a 12-year-old male (pony 1) and a 27-year-old female (pony 2), were referred for right eye enucleation due to a perforating corneal ulcer and severe recurrent uveitis, respectively. Pony 1 was stressed, had lung stridor and hyperthermia, and developed inspiratory dyspnoea with handling. Radiography confirmed collapse of the entire trachea as well as inflammation of the lower airways. Corticosteroids and bronchodilators were administered by nebulisation for 1 week before surgery. Pony 2 had a grade III/VI mitral murmur and a clinical history of oesophageal obstructions and tracheal collapse requiring tracheostomy. Both ponies were premedicated with acepromazine and xylazine; anaesthesia was induced with midazolam and ketamine. Nasotracheal intubation was performed in left lateral recumbency with extension of the neck and head and was guided by capnography. The nasotracheal tube consisted of two endotracheal tubes attached end-to-end to create a tube of adequate length and diameter. Pony 2 was orotracheally intubated during surgery and later reintubated with a nasotracheal tube. Anaesthesia was maintained with isoflurane using volume-controlled ventilation. Analgesia was provided by a retrobulbar blockade with mepivacaine and lidocaine. Cardiovascular support consisted of lactated Ringer’s solution and dobutamine. After surgery, the ponies were administered xylazine and supplemented with oxygen through the nasotracheal tube. Recovery was assisted by manual support of the head and tail. Successful extubation was achieved following butorphanol administration after approximately 1 hour in standing position. Both ponies were discharged from the clinic a few days after surgery.